2022
DOI: 10.1039/d2ee01850k
|View full text |Cite
|
Sign up to set email alerts
|

A trade-off between ligand and strain effects optimizes the oxygen reduction activity of Pt alloys

Abstract: To optimize the performance of catalytic materials, it is paramount to elucidate the dependence of the chemical reactivity on the atomic arrangement of the catalyst surface. Therefore, identifying the nature...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…[ 56 ] Besides, CN¯${\overline {{\rm{CN}}} }^*$ was recently enabled to incorporate some alloying effects, which helps elucidate the location of active sites at alloys and opens the way for new applications in electrocatalysis. [ 57 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 56 ] Besides, CN¯${\overline {{\rm{CN}}} }^*$ was recently enabled to incorporate some alloying effects, which helps elucidate the location of active sites at alloys and opens the way for new applications in electrocatalysis. [ 57 ]…”
Section: Discussionmentioning
confidence: 99%
“…An alternative is the “coordination‐activity plot” in Figure (top panel), which describes the trends in limiting ORR potentials among Pt sites in terms of CN¯$\overline {{\rm{CN}}} $. [ 69,110 ] The plot shows that it is possible to enhance the ORR activity of Pt(111) by increasing its CN¯$\overline {{\rm{CN}}} $ from 7.5 up to 8.3 (note that subsequent works refined this range to 7.5–8.0 by zooming in on the apex area [ 47,57,111 ] ). A first choice to increase CN¯$\overline {{\rm{CN}}} $ is the addition of a new nearest neighbor, such that cn increases from 9 to 10.…”
Section: Discussionmentioning
confidence: 99%
“…160 Continuous development of high-performance material systems with acceptable prices and properly optimized cell structure designs are critical for increasing the stack power density. For basic material development, novel Ptbased catalyst systems with modified compositions and structures are highly capable of boosting the specific activity and stability, such as Pt alloys, [161][162][163][164] strained Pt electrodes, 165 microstrained Ptbased catalysts, 166 Pt nanostructures, 167,168 and Pt concave nanoparticles and cavities. 169,170 In addition, carbon-based materials doped with nitrogen and transition metals have made impressive achievements in replacing Pt-based catalysts for fuel cells.…”
Section: Hydrogen Usementioning
confidence: 99%
“…Under the combined influence of the ligand effect and the strain effect, the PtM alloy exhibited the best catalytic activity at Pt 3 N, consistent with the volcanic diagram. 68,69 Loffreda et al found that adding/removing Pt neighbors and compressing/stretching the Pt-Pt distance also changed the d-band center energy and the binding energy, well describing and predicting the chemical reactivity of pure metals. 70 In summary, these studies are usually based on the following aspects: (1) enhancing the catalytic activity theoretically by d-band, Pt-Pt distance, and coordination number adjustment;…”
Section: Pt-based Orr Catalysts With Supportsmentioning
confidence: 99%